DETERMINING WELLS CANDIDATES FOR HOLE CLEANING IN A KAMOJANG GEOTHERMAL FIELD - Nugraha, Farhan; Laksmita, Riska (Journal of Petroleum and Geothermal Technology, 2025)
During the generation for more than 40 years, Kamojang wells have experienced decline in production. It directly affects steam supply to the power plant. The most important program to resolve steam availability is to drilling makeup well. Limited access and unsuccessful drilling makeup well as expected in the last 10 years becomes a problem in order to maintain long term production. Fetkovich Method has been used as guideline to simulate gas/geothermal well production performance. It has been used widely and give an accurate model of production performance. But, there is a weakness in Fetkovich Method, which is it’s difficult to understand the change of parameter stabilization production coefficient and deliverability exponent with their correlation in wellbore or reservoir.  Acuna and Pasaribu (2008) can handle this problem with anaylitical method through parameter of friction coefficient inwellbore and productivity index in reservoir. In this case, Hole cleaning aims to dissolve scaling that cause decline of production. As result total of seven wells experienced increase in production after hole cleaning. It gains approximately 8 MW. In addition, the advantages of this jetwash are reduction in cost and time as well compared.